2022
DOI: 10.1071/hc21166
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the maternal vaccination journey and influencing factors for Māori women in Aotearoa New Zealand: a qualitative study

Abstract: Introduction. Uptake of maternal vaccinations (MVs) is suboptimal in Aotearoa New Zealand, particularly for Māori. Aim. To describe Māori women's journeys regarding maternal pertussis and influenza vaccinations and explore influences on uptake. Methods. Semi-structured interviews were conducted in Waikato, Aotearoa New Zealand, with pregnant or recently pregnant Māori women, and separately with Māori healthcare professionals (HCPs) to understand women's decisions regarding MVs and enablers and barriers to upta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Participants identified that accessible and suitable venues for vaccination were important to improve patientcentred care and facilitate vaccination, and that child-friendly environments and easy-to-access drop-in centres would be of use for some pregnant women/people. Other Aotearoa NZ studies also found that pregnant women/people needing to take time off work or arrange for childcare whilst they go to an appointment to receive vaccination may be barriers too difficult to overcome (Duckworth, 2015;Gauld et al, 2022a). Furthermore, a lack of transport and costs for accessing services (e.g., buses, taxis, and accounting for unpaid bills) have also been previously described as barriers (Duckworth, 2015;Healy et al, 2015).…”
Section: System Improvements To Support Vaccinationmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants identified that accessible and suitable venues for vaccination were important to improve patientcentred care and facilitate vaccination, and that child-friendly environments and easy-to-access drop-in centres would be of use for some pregnant women/people. Other Aotearoa NZ studies also found that pregnant women/people needing to take time off work or arrange for childcare whilst they go to an appointment to receive vaccination may be barriers too difficult to overcome (Duckworth, 2015;Gauld et al, 2022a). Furthermore, a lack of transport and costs for accessing services (e.g., buses, taxis, and accounting for unpaid bills) have also been previously described as barriers (Duckworth, 2015;Healy et al, 2015).…”
Section: System Improvements To Support Vaccinationmentioning
confidence: 99%
“…Some pregnant women/people often remain unvaccinated in Aotearoa NZ and internationally because they do not receive information about vaccinations in pregnancy (Donaldson et al, 2015;Gauld et al, 2016;Young et al, 2022). Other barriers include limited access to care, lack of transport to vaccination venues, costs involved with vaccination and time pressures (Duckworth, 2015;Gauld et al, 2022a;Gauld et al, 2022b;Hill et al, 2018;Larson et al, 2014;Wilson et al, 2015). Unfortunately, some barriers (such as cost and transport issues) are likely to affect those most vulnerable to poor health outcomes in the community and thus worsen existing health inequities.…”
Section: Aotearoa New Zealand Research Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…A qualitative study by Gauld and colleagues found that Māori women experienced barriers to uptake of maternal pertussis and influenza vaccinations, including sometimes being insufficiently informed by their healthcare providers of the benefits. 10 Solutions include pharmacists assisting in raising awareness of maternal vaccinations and access, early engagement with midwives, and improving accessibility through funding transport. Jardine and others found that pregnant Māori women may experience barriers to engaging with a midwife and are hopeful that the online tool, Best Start Kōwae, will help reduce this equity gap.…”
Section: From the Editors: Challenges And Opportunities For Sustainab...mentioning
confidence: 99%